The concept and application of ḍamān al-milkiyyah (ownership risk): Islamic law of contract perspective - Lutfi Abdul Razak; Muhammad Nabil Saupi (ISRA International Journal of Islamic Finance, 2017)
Purpose: The purpose of this paper is to elucidate the concept of ḍamān al-milkiyyah (ownership risk) and to assess its application in contemporary Islamic financial products and services. Design/methodology/approach The methodology adopted is that of descriptive research. Findings From an Islamic law of contract perspective, the concept of ḍamān al-milkiyyah is central to legitimate profit-making transactions and hence must be adhered to in practical applications of Islamic finance. Research limitations/implications This study should help motivate further investigation into the position of ḍamān al-milkiyyah among different parties in existing Islamic financial products and services. Practical implications Policymakers and regulators should ensure that Islamic financial products and services are structured in a way that does not allow parties to profit without adequately bearing the liability for potential loss. Social implications The condition of ḍamān al-milkiyyah as a source of legitimate profit reflects the idea that the role of finance in Islam is to promote and ensure social benefits. Originality/value This paper emphasizes the importance of ḍamān al-milkiyyah as a fundamental condition for profit in Islamic financial transactions.
Keywords: 330; ḍamān al-milkiyyah; liability; ownership; responsibility; Risk; uncertainty